Debris Flow Modelling Using RAMMS Model in the Alpine Environment With Focus on the Model Parameters and Main Characteristics - Mikoš, Matjaž; Bezak, Nejc (Frontiers in Earth Science, 2021)
Debris flows are among the natural hazards that can occur in mountainous areas and endanger people’s lives and cause large economic damage. Debris flow modelling is needed in multiple applications such as design of protection measures or preparation of debris flow risk maps. Many models are available that can be used for debris flow modelling. The Rapid Mass Movement Simulation (RAMMS) model with its debris flow module, (i.e. RAMMS-DF) is one of the most commonly used ones. This review provides a comprehensive overview of past debris flow modelling applications in an alpine environment with their main characteristics, including study location, debris flow magnitude, simulation resolution, and Voellmy-fluid friction model parameter ranges, (i.e. μ and ξ). A short overview of each study is provided. Based on the review conducted, it is clear that RAMMS parameter ranges are relatively wide. Furthermore, model calibration using debris-flow post-event survey field data is the essential step that should be done before applying the model. However, an overview of the parameters can help to limit the parameter ranges. Particularly when considering the similarity between relevant case studies conducted in similar environments. This is especially relevant should the model be applied for estimating debris-flow hazard for potential future events. This model has been used mostly in Europe, (i.e. Alpine region) for modelling small and extremely large debris flows.